Clinical features and genetic analysis of a Brazilian patient with sitosterolemia: a case report - Felipe Augusto Azevedo Leão; Leticia Ferreira Gontijo Silveira; Rodrigo Rezende Arantes; Milena Maria Moreira Guimarães (Archives of Endocrinology and Metabolism, 2025)
ABSTRACT Sitosterolemia is a rare genetic lipid disorder caused by mutations in the ABCG5/ABCG8, genes. It is characterized by plasmatic plant sterols accumulation, formation of tendon and tuberous xanthomas and early onset coronary artery disease. The differential diagnosis with other congenital dyslipidemias presents significant challenges. We describe a case of a male patient who presented with hypercholesterolemia and tendinous xantomas from the age of 5. The patient was born to consanguineous parents, with no family history of hypercholesterolemia. With the initial hypothesis of cerebrotendinous xanthomatosis, he was treated with chenodeoxycholic acid, which yielded no improvement. Over time, he developed persistent thrombocytopenia and arthralgia, and experienced an acute myocardial infarction at the age of 27. Genetic analysis revealed the previously known p.Trp361*mutation in homozygosity in the ABCG8 gene and was negative for CYP27A1 variants, associated with cerebrotendinous xanthomatosis. The subsequent introduction of a diet with vegetable fats restriction and administration of ezetimibe resulted in an excellent response. The diagnosis of congenital hypercholesterolemia is challenging due to the low prevalence and heterogenous presentation of the condition. This case underscores the importance of clinical suspicion and the confirmation of the molecular diagnosis for a precise therapeutic management.